Work style reform: the impact of organisational factors on work-life balance amongst Japanese employees - Sagegami, Tomoko (2018)
Work-life balance (WLB) has been considered an important factor not only in terms of individual happiness, but also from perspectives of organisational performance and solutions to social issues such as low birth rate, insufficient participation of female workers and shortage of labour. However, WLB in Japan has not been improved and the working environments remain unchanged. A culture of long working hours forces employees to spend less time on family life. Lack of adaptation to flexible working styles prevents them from achieving a better WLB. Existing literatures highlights the influence of organisational culture on employees’ WLB and work styles. Japanese government launched a new initiative named “Work Style Reform” in 2016 to ameliorate the current situation. This study explores the impact of organisational factors towards improving individual WLB in the context of Japanese working environments, while also considering possible influence of Work Style Reform. Relevant organisational factors include working hours, work flexibility and organisational culture. Primary data was collected by quantitative online survey as well as qualitative semi-structured interviews. Then, descriptive and inferential statistical analyses of online survey results were conducted using IBM SPSS version 23 to test the hypotheses. The results revealed that long working hours have a strong and negative correlation with WLB, while work flexibility has a slightly positive relationship with WLB. With regards to organisational culture, Clan culture, which has family-like and corporative elements, positively influences on employees’ WLB. On the other hand, it was found that the characteristics of innovative and creative Adhocracy culture have positive correlation with work flexibility. Survey results also identified a significant gap between what “Work Style Reform” promotes and actual working environments in respondents’ organisations. In addition, the open-ended feedback and semi-structured interviews showed that the mind-sets of Japanese people affect their work styles. These findings were then used to generate three recommendations for successful implementation of work style changes: review and redesign of business processes, an effective implementation plan and collective impact, which includes government intervention, social support and organisational initiatives. In conclusion, accepting diversity in work styles will enable individuals to determine how they live and work depending on their needs, and ultimately lead to diversity in life styles in our society.